MANAJEMEN PROGRAM KAJIAN MASJID RAYA HUBBUL WATHAN ISLAMIC CENTER NUSA TENGGARA BARAT - Lalu Adam Zikrullah (Mudabbir: Jurnal Manajemen Dakwah, 2023)
This article examines Islamic programs at the Hubbul Wathan Islamic Center Mosque in Mataram, NTB, with a focus on looking at the implementation of management functions in each program held. In this article, there are several questions that are attempted to be answered, namely, what kind of and how is the management function implemented in every Islamic program at the Great Mosque of Hubbul Wathan Islamic Center, NTB? NTB Center.? This article is the result of field research and uses a qualitative approach. Regardless, the data in this article are sourced from primary and secondary data which are processed through observation, structured interviews, and documentation. The results of this study indicate that the implementation of the management function in every Islamic program at the Hubbul Wathan Islamic Center Islamic Center NTB Mosque has been well implemented. This matter is clearly seen in the process of implementing Islamic programs such as, among other things, planning before the study program, organizing tasks between related fields, carrying out tasks according to planning, and monitoring in the form of evaluating activities that have been carried out. Meanwhile, the background of the implementation of the management function of this activity is to facilitate and fulfill the community's needs regarding religious knowledge. However, even though the management functions have been well implemented, the local government's support for the implementation of Islamic studies programs appears to have not been maximized, particularly with regard to the accommodation of pilgrims